Peculiarities of Trade Secrets Protection in Public Procurement - Birštonas, Ramūnas; Šimanskis, Karolis (Teisė, 2019)
This article deals with the legal regulation of the obligation to protect confidential information in public procurement procedures and the peculiarities of the application of trade secrets in these relations.